The upper pleistocene deglaciation on the apennines (Peninsular Italy) [La deglaciación del Pleistoceno Superior en los Apeninos (Península Italiana)] - Giraudi, C. (Cuadernos de Investigación Geográfica, 2015)
The synthesis of the published data and new researches allow to establish a more reliable chronology of the phases of deglaciation that occurred after the Apennine last glacial maximum. The chronological framework was assured by radiocarbon dating and by the presence of four geochemically and chronologically characterized tephra layers and a quartz-rich loess, that were found on different mountain massifs, mainly in Central Italy. After the Campo Imperatore Stade (local LGM) dated 28-27 ka cal BP, a first retreat took place during the Campo Felice Arid Spell, followed by a glaciers advance (Le Capannelle Stade) that started between 26 and 25 ka cal BP. During the readvance the glaciers reached a length about 90% of the local LGM glacier. The readvance was followed by a retreat broken by at least two readvances (Piano Pietranzoni and Lago Pietranzoni readvances) and then by a very fast withdrawal at the beginning of the Fornaca Interstade, dated ca. 22-21 ka cal BP. The Fontari Stade glacier’s advance began ca. 18 ka cal BP and was followed by a retreat broken by at least three small readvances (Fontari 2; Fontari 3; M. Aquila 1). The M. Aquila 1 readvance ended ca. 15-14 ka cal BP. The Venaquaro Interstade, dated 14-13 ka cal BP, was followed by the M. Aquila Stade. This stade was the last Late Pleistocene small glacial expansion and can be correlated to the Younger Dryas. The variations in the atmospheric circulation in the Mediterranean area likely played a role during the first deglaciation phases (between 27-26 and 21-22 ka cal BP). During the period between 19-18 and 12 ka cal BP the glacial fluctuations were linked, very likely, to the climatic impact of the North Atlantic ice rafted debris events. It is possible, therefore, that during the Fornaca Interstade (between 22-21 and 19-18 ka cal BP), there has been such a change in atmospheric circulation and the Central Mediterranean area became more prone to be influenced by the effects of the North Atlantic D/O and IRD events. © Universidad de La Rioja.